The impact of school violence on secondary victims in selected secondary schools in TandT [PowerPoint presentation] - James, Freddy; Glasgow-Charles, Kimberly; Williams, Dianne; Keith, Lyn (My University, 2013)
Although a wide body of research on school violence exists, much of the work is concentrated within westernized contexts, particularly within the American context, and is focused on: the types of violent behaviours exhibited, the causes of the behaviour, and solutions to reduce the behaviours. Within the local context, research done identifies root causes of school violence and possible solutions. These local studies neither purposely focus on the unmet needs of the secondary victims of school violence nor devise programmes to address the needs of this group of victims. The purpose of the current research is to fill this gap by engaging in a study that examines the impact of school violence on students who are secondary victims, and using their voices to create interventions to improve their school experiences and, as a corollary, their achievement. The research is situated within the fields of criminology and school improvement and the paper presents findings from two schools
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Secondary school students; Secondary victims; School violence; Psychosociology; Psychological effects; Intervention programmes; Conference papers; Trinidad and Tobago